Discourse Analysis of The Film Entitled “Dirty Vote” Using Van Dijk’s Model - M. Fathoni; Zahratul Fikni; Ayu Surayya; Muhamad Husnu (Journal on Education, 2024)
This research is discourse analysis research on the film directed by Dandhy Dwi Laksono entitled "Dirty Vote". This research falls into the category of reaserch literature. Data from this study was taken from a youtube chennel called Dirty Vote by noting points that are important to analyze. The data was analyzed using qualitative descriptive methods. The data was revealed using Van Dijk's discourse analysis model. He expressed it in three dimensions, namely text, social cognition, and social condition. This study aims to reveal socio-political criticism in this film in the dimension of text analysis, then reveal social cognition, and reveal social condition. In the text dimension discuss macrostructure, superstructure, and microstructure. Then the social cognition dimension discusses the view of the film and the social condition dimension discusses the relationship of this film with the current state of society. Based on the analysis, there was a socio-political criticism contained in the film entitled "Dirty Vote". This is evidenced by the choice of words, direct criticism, and the use of sentences used in text